2015
DOI: 10.1049/iet-cta.2014.0202
|View full text |Cite
|
Sign up to set email alerts
|

Non‐singular fixed‐time terminal sliding mode control of non‐linear systems

Abstract: This study addresses a fixed-time terminal sliding-mode control methodology for a class of second-order non-linear systems in the presence of matched uncertainties and perturbations. A newly defined non-singular terminal sliding surface is constructed and a guaranteed closed-loop convergence time independent of initial states is derived based on the phase plane analysis and Lyapunov tools. The simulation results of a single inverted pendulum in the end are included to show the effectiveness of the proposed met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
258
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(295 citation statements)
references
References 30 publications
2
258
0
Order By: Relevance
“…Different from Zuo's approach [51], the proposed control scheme extends fixed-time stable control to high-order nonlinear system and achieves semiglobally fixed-timely uniformly ultimately bounded stabilization.…”
Section: Remarkmentioning
confidence: 99%
See 1 more Smart Citation
“…Different from Zuo's approach [51], the proposed control scheme extends fixed-time stable control to high-order nonlinear system and achieves semiglobally fixed-timely uniformly ultimately bounded stabilization.…”
Section: Remarkmentioning
confidence: 99%
“…This advantage promotes practical application of fixed-time stability, and it has been applied to design uniform robust exact differentiator [48] and address network consensus problem for multi-agent system [49,50]. In [51], a nonsingular fixed-time terminal sliding mode control was designed for second-order system. However, the existing results of fixed-time stable control scheme are only limited to low-order systems, and it is nontrivial to extend the fixed-time stable control to high-order systems.…”
Section: Introductionmentioning
confidence: 99%
“…A fixed‐time attitude tracking controller is developed based on Sin‐FM in Reference . Two fixed‐time attitude controllers are given based on ASMM for attitude stabilization and attitude tracking in References , respectively. As mentioned in the above paragraph, TSM methods have some weaknesses.…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome these shortcomings, a new concept named fixed-time synchronization was firstly taken into account in [19]. Hints for future research on the fixed-time synchronization problem can be found in [20][21][22][23][24][25]. By designing a sliding mode controller, the fixed-time synchronization issue for complex dynamical networks was addressed in [21].…”
Section: Introductionmentioning
confidence: 99%